RESOLUSI KONFLIK AKIBAT UJARAN KEBENCIAN DI MEDIA SOSIAL BERBASIS KEARIFAN LOKAL DI BALI - Zaenal Eko Eko (Harmoni, 2021)
It is a matter of fact, people, culture and religion in Bali mingle into one single entity and contribute to the tourism industry which began to rise in the 1970s. The increasing tourism industry has been attracting job seekers from all over Indonesia, even abroad, to work in Bali. As a result, Bali with certain areas such as Denpasar, Gianyar and Tabanan is known as a multicultural area. This is where both Balinese natives who are Hindus, as well as immigrants who are not Hindus interact with each other. With the massive use of social media, the expression of opinions emerges which the uploader sometimes does not realize the impact of uploading social media content. This article aims to describe the impact of social media in a pluralistic society and the sensitive issues related to diversity in Bali. The article resulted from field research using qualitative method shows that the use of social media poses a threat to plural society as long as it is used to express religious and ethnic hatred, especially regarding the sacred religious rituals. On the other hand, the use of social media to gain electoral support by raising the issue of threatened local majority also endangers non Hindu population. The results of this study indicate that tensions arising from social media contents in Bali can be decreased by mediation using local wisdom, rather than national laws.